SHAMKHAL TARKOVSKY, THE BIGGEST LANDOWNER OF FEUDAL DAGESTAN - Aliev, B G (History, Archeology and Ethnography of the Caucasus, 2016)
The article is devoted to land ownership of Shamkhal Tarkovsky, the biggest landowner in feudal Dagestan. The author analyzes the types of land ownership and the kinds of land, which Shamkhal possessed, considers the ways the land was used and the resulting forms of dependence relation, particularly rent relations, and stresses the special role of pasture rents. Basing on the specific materials, the author shows the income of Shamkhal from the various kinds of land. The author emphasizes the special role of roofless stone shelters, which mountain communities of Dagestan rented and paid for them in kind and money and rendered various services and assistance to Shamkhal. Shamkhal’s land ownership contributed to his high position, authority, influence and respect among other feudal rulers in Dagestan and beyond.